Peculiarities of absorption spectra of solid solutions of CsAg₂l₃-CsCu₂l₃ complex compounds - Miloslavsky, V.K.; Yanakova, O.N.; Kovalenko, E.N. (Functional Materials, 2007)
The low-frequency electron absorption spectra in thin films of Cs(Ag₁₋ₓCuₓ)₂l₃ solid solutions have been investigated. At the fundamental band edge, two exciton bands A₀ and A₁ are observed, and the parameters thereof (spectral position, half-width and oscillator strength) have been found in the 0≤xl range. From the concentration dependence of those parameters, the A₀ and A₁ excitons have been established to be localized in the double chains consisting of tetrahedrons MI₄ (M = Ag, Cu) and being a structural elements of CsM₂I₃ crystal lattice. Experimental results are discussed assuming the hybridization Ag, Cu d-orbitals and I p-orbitals in the upper valence band of the compounds and dependence of hybridization on molar concentration x.